2011
DOI: 10.1098/rsta.2010.0325
|View full text |Cite
|
Sign up to set email alerts
|

Interfaces and inhomogeneous turbulence

Abstract: A Euromech colloquium, on interfacial processes and inhomogeneous turbulence, was held in London on 28-30 June 2010. Papers were presented describing and analysing the influence of interfaces that separate turbulent/non-turbulent regions, between regions of contrasting fluid properties, or at the edge of boundaries. This paper describes a summary of the work presented, giving a snapshot of the current progress in this area, along with discussions about future research directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 71 publications
(111 reference statements)
3
24
0
Order By: Relevance
“…It should be noted that internal layers are not solely characterized by regions of intense shear; there may also be internal layers without significant shear. 2 Internal layers and the T/NT interface are shown to have similar characteristics and can be described by the same theoretical framework. By quantifying the entrainment over the bounding shear layers, growth rates of the associated large scale regions can be estimated, which is analogous to the overall TBL growth by the entrainment across the T/NT interface.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…It should be noted that internal layers are not solely characterized by regions of intense shear; there may also be internal layers without significant shear. 2 Internal layers and the T/NT interface are shown to have similar characteristics and can be described by the same theoretical framework. By quantifying the entrainment over the bounding shear layers, growth rates of the associated large scale regions can be estimated, which is analogous to the overall TBL growth by the entrainment across the T/NT interface.…”
Section: Introductionmentioning
confidence: 92%
“…2,14 Recently, internal layers with similar characteristics as a T/NT interface within homogeneous isotropic turbulence were reported by Ishihara et al 5,6 According to Robinson 15 (and references therein), internal shear layers have been observed throughout TBLs as well, even in the outer region of the flow. For instance, Blackwelder and Kovasznay 16 showed that significant shear layers were observed upstream of large scale motions based on space-time correlations of hotwire data in a TBL.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Finally, following a successful Euromech 517 meeting on interfaces in turbulent flows, Hunt et al [8] describe a timely review of the presentations and a discussion of the broad outstanding questions in this area. The research community in this area is beginning to make significant inroads in this topic, as seen from the collection of papers in this Theme Issue.…”
Section: Organization Of Issuementioning
confidence: 99%
“…Dilution caused by entrainment at the edge of the jet or plume has been studied in detail over the last 50 years. Nevertheless, there is a debate on the detailed elements of entrainment, such as on the dominance of nibbling versus engulfment (Hunt, Eames & Westerweel 2006;Hunt et al 2011). Theoretical models on jets and plumes (List 1982) are usually based on the conceptual framework of Morton, Taylor & Turner (1956), which has been extended to include the effects of momentum, buoyancy and sources varying in time (Scase, Caulfield & Dalziel 2006a;Scase et al 2006b), non-Boussinesq behaviour (Woods 1997) and internal generation of buoyancy (Hunt & Kaye 2005).…”
Section: Introductionmentioning
confidence: 99%